Aksjologiczny profil starości w polszczyźnie na podstawie danych korpusowych - Polkowska, Laura (Załącznik Kulturoznawczy, 2024)
The Axiological Profile of Old Age in the Polish Language Based on Corpus Data In this sketch, an attempt is made to reconstruct the axiological profile of old age in the Polish language. The linguistic material is sourced from the National Corpus of Polish, currently the most representative text database for Polish language users. This text serves as an introduction to the reconstruction of the linguistic picture of old age, presenting essential considerations on the evaluation of the concept. The analysis reveals that old age is primarily conceptualized through metaphors (such as OLD AGE IS A HEAVY OBJECT, OLD AGE IS AN ENEMY) and is positioned among anti-values due to lexical-semantic associations and so-called “contagious conjunctions”.